Self-compassion as a moderator of the relationships between shape and weight overvaluation and eating disorder psychopathology, psychosocial impairment, and psychological distress. (June 2020) - Linardon, Jake; Susanto, Luvena; Tepper, Hannah; Fuller-Tyszkiewicz, Matthew
Highlights: Tested the moderating role of self-compassion on overvaluation of weight and shape and psychopathology. Cross-sectional data analyzed from 608 women and 366 men. Self-compassion attenuated overvaluations' links with key dependent variables. Nurturing self-compassion could protect against adverse outcomes. Abstract: Shape and weight overvaluation is a core component of body image theorized to drive many of the symptoms of eating disorders (ED) and associated distress and impairment. Identifying variables that protect against the negative effects of shape and weight overvaluation is needed for informing primary intervention targets. Self-compassion may be a protective factor given its role as an adaptive affect regulation strategy. We thus examined whether self-compassion would attenuate the relationships between shape and weight overvaluation and ED psychopathology, psychosocial impairment, and psychological distress. Cross-sectional data were analyzed from 992 (619 women and 373 men) participants. Multiple regression analyses revealed that self-compassion moderated the relationship between shape and weight overvaluation and each dependent variable. Specifically, among men and women with lower levels of self-compassion, overvaluation of shape and weight was strongly associated with each of the criterion variables; however, these relationships were either absent or weaker among those with higher levels of self-compassion. Present findings suggest that it may be beneficial for ED prevention and early intervention programs to explicitly incorporate components of compassion-focused interventions to improve mental health outcomes among the general public.